Studying the magnetic susceptibility of ceramic used in construction materials in Syria (Journal of Hama University, 2020)
The magnetic susceptibility of ceramics samples were measured in terms of the magnetic field ,the frequency of the magnetic field and the sample geometry.The samples were in the form of cubes and cylinders in different dimensions. The ceramic samples were taken from wall ceramics and floor ceramics. The result of the measurements using ac susceptometer showed that the magnetic susceptibility of the wall ceramics were in the range from 0.009 and 0.028 and the magnetic susceptibility of the floor ceramic were in the range from 0.003 and 0.0072. The difference between these two values is due to the chemical composition of wall ceramic and floor ceramic where the ratio of (Al2Si2O5(OH)4)  in the wall ceramic is greater than that of the floor ceramic. As a result of the research it was found the susceptibility of these samples is independent of the applied magnetic field in the range (0.53 – 1.5) mT and also independent of the frequency in the rang (65-302)Hz. It was found that there is no effects  of the sample geometry on the magnetic susceptibility.